A study on impact behaviour of a novel oil palm fibre reinforced metal laminate system - Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Selamat, Mohd Zulkefli; Said, Md Radzai; Subramonian, Sivarao (ARPN Journal of Engineering and Applied Sciences, 2016)
Recently, researchers and industries have shown an increased interest in, natural fibres due to their advantages compared to synthetic fibres as it is environment friendly and low cost engineering materials. Low velocity impact response of fibre metal laminate (FML) based on short oil palm empty fruit bunch fibres according to weight percentage of 0%, 10%, 20%, 30%, 50% and 60% has been investigated. The specimens were prepared and tested using impact pendulum tester according to ASTM E-23 standard. The impact resistances of the various laminates were benchmarked with monolithic aluminium. Flat wise impact energy is almost equivalent with monolithic aluminium. This work shows that this type of FML can be used as a substitute to aluminium panels.